PENGARUH PENGAWASAN, TARIF CUKAI, DAN BATASAN MINIMUM HARGA JUAL ECERAN TERHADAP TANGKAPAN ROKOK ILEGAL - Gede Dwipa Ria Narasara; Diah Widyawati (Bina Ekonomi, 2023)
Illegal cigarettes are very dangerous, both for health and for state revenue, so DJBC, as the agency authorized to oversee the circulation of cigarettes, must catch illegal cigarettes to suppress the circulation of illegal cigarettes in the future. The purpose of this study was to determine the effect of supervision, excise tariffs, and minimum HJE limits on illegal cigarette catches in Indonesia. The authors carried out a descriptive analysis of the realization of supervision budget data, number of DJBC employees, excise rates, minimum retail selling price limits, and catches of illegal cigarettes. The authors obtained these data from the Directorate General of Customs and Excise and from the Central Bureau of Statistics. The result is that the increase in excise rates and the minimum HJE limit in Indonesia so far have not had a significant impact on illegal cigarette catches. The only thing the government can do to suppress the circulation of illegal cigarettes is to strengthen supervision by increasing the supervision budget and human resources, both in terms of quantity and quality. Tightening the overall supervision will be able to optimize the catch of illegal cigarettes and reduce the circulation of illegal cigarettes in the future.